2014
DOI: 10.1108/cms-04-2014-0089
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, work stress and employee behavior

Abstract: Purpose – This paper aims to explore the influences of leadership and work stress on employee behavior, and the moderating effects of transactional and transformational leadership on the relationship between work stress and employee negative behavior. Design/methodology/approach – Using convenience sampling method, the authors investigated employees from 20 firms in different places and industries, and 347 valid questionnaires were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Therefore, TMS has a moderating effect on the relationships between the knowledge and the attitude of user managers with the ISP of the department. Similarly in the context of human resource management, research has shown that supervisors' leadership interacts with subordinates' work attitude in predicting subordinates' JP (Yao et al, 2014). Based on the above discussion, we propose the following two hypotheses.…”
Section: Research Model and Hypothesesmentioning
confidence: 91%
“…Therefore, TMS has a moderating effect on the relationships between the knowledge and the attitude of user managers with the ISP of the department. Similarly in the context of human resource management, research has shown that supervisors' leadership interacts with subordinates' work attitude in predicting subordinates' JP (Yao et al, 2014). Based on the above discussion, we propose the following two hypotheses.…”
Section: Research Model and Hypothesesmentioning
confidence: 91%
“…It involves tolerance of complexity and ambivalence. Yao et al [45] related complex situations and levels of stress with transformational leadership. Based on this theory the following hypothesis is presented:…”
Section: Tolerance and Leadershipmentioning
confidence: 99%
“…Their results also indicated that the styles most used by managers were accommodation and collaboration. Yao et al (2014) explored the relationship between leadership, work stress and employee behaviours. A secondary aim of their research was to investigate the moderating effects of transformational leadership in the relationship between work stress and employees' negative behaviour.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%